Minimizing Blood Loss and Transfusions in Total Knee Arthroplasty - White, Charles Cody, IV; Eichinger, Josef K.; Friedman, Richard J. (The Journal of Knee Surgery, 2018)
Blood loss management is critical to positive outcomes in patients undergoing total knee arthroplasty (TKA). Transfusions are associated with an increased risk of major and minor adverse events, length of hospitalization, and overall cost associated with surgery. Many techniques have been investigated and compared. Tranexamic acid (TXA), an antifibrinolytic drug widely known to reduce blood loss, may be a bridge to the goal of eliminating blood transfusions from TKA. Administration of TXA can be performed intravenously, topically at the knee joint, orally, or in combination. A single bolus or multiple doses have reduced total blood loss and transfusion rates consistently, safely, and cost-effectively. The uptake in use of TXA by surgeons has been slow due to concerns in patients deemed high risk for thromboembolic events. Newer evidence from studies specifically involving high-risk patients demonstrates that TXA is indeed safe in this cohort and provides benefits that greatly outweigh potential risks. Incorporation of TXA as a routine part of TKA is in the best interest of patients, health care teams, and medical institutions. TXA can be employed seamlessly with other blood saving techniques and has the capacity to increase productivity and decrease overall cost. This can be achieved by reducing the incidence of transfusion and length of stay, and the need for practices such as preoperative anemia treatment and suction drainage.
Keywords: total knee arthroplasty; tranexamic acid; blood management; transfusion